Willingness to pay for a new biopesticide to control mango fruit flies - Tassembedo, Boureima; Ouedraogo, Mathieu; Nebie, Karim; Sinzogan, Antonio Alain Coffi; Toe, Patrice (2024)
Purpose. This study aimed to examine the willingness to pay (WTP) of mango farmers for a new biopesticide to control fruit flies in western Burkina Faso. Methodology / approach. This study is based on the example of mango farmers in Western Burkina Faso, which is the largest mango-producing area in the country. This research used a multistage sampling technique, the first of which involved selecting two regions where mango production is predominant and where late varieties are highly susceptible to fruit fly attack. In the second stage, three provinces were reasonably selected: Kénédougou, Comoé, and Houet in the west of the country. To achieve this goal, a cross-sectional data were gathered from a sample of 341 mango growers. The contingent valuation method was applied and the Cragg Double-Hurdle model was used for analysis. Furthermore, primary data was obtained from respondents through interviews, and secondary data was obtained from relevant agencies. Results. The results indicate that 81.52 % of growers are willing to pay an average of FCFA 2,745 and 70.38 % of them proposed an average amount to be paid of FCFA 2,851 for a weekly treatment with the new biopesticide. Education, access to advisory services, knowledge of fruit flies, and organic production methods influence both growers’ decision to pay and the value of their WTP. Additionally, the willingness to pay for the new biopesticide is positively influenced by the farming area and the perception of the detrimental effects of chemical pesticides on human health and the environment, while the decision to adopt is positively influenced by the income generated from the production of mangos. Knowledge of WTP and its determinants will make it possible to put in place appropriate and effective mechanisms for disseminating information on the new biopesticides to improve fruit fly control and, in turn, farmers’ production and income. Originality / scientific novelty. Despite the threat posed by fruit flies to the mango industry, no studies in Burkina Faso have examined the willingness to pay for methods to control these pests. The novelty of this research is in its application of the Cragg Double-Hurdle analytical model in an ex-ante setting for a new biopesticide. This is the first time that the price farmers are willing to pay for a new fruit fly control method and the factors that determine its use have been scientifically assessed before it is introduced to the market in Burkina Faso. Policymakers and other stakeholders will be able to use the analytical results to promote the new biopesticide for widespread use, as opposed to conventional control approaches. Practical value / implications. To effectively control fruit flies, it is necessary for decision makers to work closely with the private sector to make the yeast waste-based biopesticide for fruit fly control affordable by creating incentives for its multiplication and distribution. Extension services should also be involved in promoting this technology to growers. Finally, awareness-raising campaigns for growers on fruit fly damage and the biopesticide for successful collective control should be stepped up.